1987
DOI: 10.1002/bjs.1800740226
|View full text |Cite
|
Sign up to set email alerts
|

Gangrene of the right colon: A rare complication of trauma-related systemic hypotension

Abstract: Correspondence to: Mr M. M. W. Parry, Department of Surgery, Groote Schuur Hospital, Observatory, Cape Town 7925, South Africa Hypotensive ischaemia of the colon has been described associated with non-abdominal trauma', congestive cardiac failure* and pancreatitis3. This usually causes merely mucosal damage and only ten cases of gangrenous colon associated with systemic hypotension from non-abdominal trauma have been reported in the English literature. Case reportA previously healthy 16-year-old boy sustained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Renton [18] was the first to report intestinal infarction after trauma in a previously healthy young patient. Parry et al [19] suggested that an anatomic abnormality of the mesenteric circulation might account for the right-sided necrosis. Early anatomic work done by Drummond [20], showed poor development of the marginal artery to the right colon in one-quarter of the specimens examined.…”
Section: Discussionmentioning
confidence: 99%
“…Renton [18] was the first to report intestinal infarction after trauma in a previously healthy young patient. Parry et al [19] suggested that an anatomic abnormality of the mesenteric circulation might account for the right-sided necrosis. Early anatomic work done by Drummond [20], showed poor development of the marginal artery to the right colon in one-quarter of the specimens examined.…”
Section: Discussionmentioning
confidence: 99%
“…Although it was not possible to determine the cause of ischemic colitis in this patient, it is speculated that a selective decrease in blood flow may have occurred in the region of the inferior mesenteric artery during hypovolemic shock soon after onset. Parry et al (10) reported a case of gangrene of the colon associated with systemic hypotension from nonabdominal trauma, and referred to 10 cases less than 30 years of age reported in the literature.…”
Section: Discussionmentioning
confidence: 99%